Writing, rewriting, and overwriting in the Books of Deuteronomy and the Former Prophets: essays in honour of Cynthia Edenburg - Ḳokh, ʿIdo; Römer, Thomas; Sergi, Omer (Ephemerides theologicae Lovanienses, 2019)
Cynthia Edenburg is one of the leading experts of the formation of the books covering Deuteronomy and the Former Prophets, commonly called ?the Deuteronomistic History?. She has renewed scholarly understanding of the process how the narrative and legal traditions that are gathered in these books were written down for the first time before they were edited in several ways by the Deuteronomistic redactors. She provided new insight into these redactional processes by distinguishing several ways of revising a text. Most of the contributions gathered in this volume pursue the question of the composition and revision of the books of Deuteronomy and the Former Prophets. Additional contributions deal with the history of the text of other books, from Genesis to Chronicles. They are all presented to Cynthia Edenburg as an appreciation of her influence on current scholarship
Keywords: Festschrift; Redaktion; Bibel / Deuteronomium